MANAJEMEN PENDIDIKAN DALAM PRESPEKTIF AL-GHAZALI : PENTINGNYA MORAL DAN SPIRITUAL - Khalimah, Nur; Rofiq, Ainur (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2024)
Education is a major pillar in the development of society and individuals, especially in the era of complex globalization. This study examines educational management from Al-Ghazali's perspective, which emphasizes the importance of integrating moral and spiritual values in education. Al-Ghazali argued that the purpose of education is not only to develop intellectually, but also to form good character and bring individuals closer to God. Through a qualitative approach and literature study, this study identified Al-Ghazali's concept of educational management, including the purpose of education, the role of educators, learning methods, educational environment, and evaluation. The results of the study indicate that holistic education must include teaching moral values, spiritual awareness, and character development. In addition, a positive educational environment and community support are essential to support the learning process. The implications of Al-Ghazali's thoughts in modern educational management include the need for integration of moral values in the curriculum, training for educators as moral role models, and holistic evaluation. By adopting this approach, it is hoped that education can produce individuals who are not only academically intelligent, but also have good morals and deep spiritual awareness, ready to face life's challenges wisely. This research provides new insights for the development of an educational curriculum that is more oriented towards character and spirituality.